Two-Color, Two-Photon Imaging at Long Excitation Wavelengths Using a Diamond Raman Laser. (5th August 2016) - Trägårdh, Johanna; Murtagh, Michelle; Robb, Gillian; Parsons, Maddy; Lin, Jipeng; Spence, David J.; McConnell, Gail
Abstract: We demonstrate that the second-Stokes output from a diamond Raman laser, pumped by a femtosecond Ti:Sapphire laser, can be used to efficiently excite red-emitting dyes by two-photon excitation at 1, 080 nm and beyond. We image HeLa cells expressing red fluorescent protein, as well as dyes such as Texas Red and Mitotracker Red. We demonstrate the potential for simultaneous two-color, two-photon imaging with this laser by using the residual pump beam for excitation of a green-emitting dye. We demonstrate this for the combination of Alexa Fluor 488 and Alexa Fluor 568. Because the Raman laser extends the wavelength range of the Ti:Sapphire laser, resulting in a laser system tunable to 680–1, 200 nm, it can be used for two-photon excitation of a large variety and combination of dyes.